2021
DOI: 10.1111/sms.13949
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antihypertensive medication and high‐intensity interval training in hypertensive metabolic syndrome individuals

Abstract: Pharmacological and non‐pharmacological therapies are simultaneously prescribed when treating hypertensive individuals with elevated cardiovascular risk (ie, metabolic syndrome individuals). However, it is unknown if the interactions between antihypertensive medication (AHM) and lifestyle interventions (ie, exercise training) may result in a better ambulatory blood pressure (ABP) control. To test this hypothesis, 36 hypertensive individuals with metabolic syndrome (MetS) under long‐term prescription with AHM t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…All of the 12 studies reported on SBP and 11 of them showed that SBP levels decreased significantly compared with the baseline, after a period of exercise training (p < 0.05) (38,39,(44)(45)(46)(47)(48)(49)(50)(51)53), only 1 study showed no significant change in SBP levels after exercise (p > 0.05) (54). Of the 9 studies reported on DBP (38,39,44,46,47,(49)(50)(51)54), only 1 study showed no significant change in DBP after exercise (p > 0.05) (49), and the other 8 studies showed DBP decreased significantly after the exercise. Subsequently, 6 studies reported on BMI (38,47,48,50,51,53), and only 2 studies showed a significant decrease in BMI after exercise (38,47,48).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…All of the 12 studies reported on SBP and 11 of them showed that SBP levels decreased significantly compared with the baseline, after a period of exercise training (p < 0.05) (38,39,(44)(45)(46)(47)(48)(49)(50)(51)53), only 1 study showed no significant change in SBP levels after exercise (p > 0.05) (54). Of the 9 studies reported on DBP (38,39,44,46,47,(49)(50)(51)54), only 1 study showed no significant change in DBP after exercise (p > 0.05) (49), and the other 8 studies showed DBP decreased significantly after the exercise. Subsequently, 6 studies reported on BMI (38,47,48,50,51,53), and only 2 studies showed a significant decrease in BMI after exercise (38,47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, 6 studies reported on BMI (38,47,48,50,51,53), and only 2 studies showed a significant decrease in BMI after exercise (38,47,48). Based on 8 studies reported on rest HR (38,39,(46)(47)(48)(49)(50)54), 6 studies showed rest HR decreased after exercise (38,39,47,48,50,54), and 2 studies showed rest HR did not change significantly after exercise (46,49). However, in the study by Lins-Filho et al, rest HR decreased significantly in the blank control group (49).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations